Immunocytochemistry of the mucilage cells of Araucaria angustifolia (Bertol.) Kuntze (Araucariaceae) - Mastroberti,Alexandra Antunes (2008)
The use of monoclonal antibodies for specific pectic epitopes is an important tool in the study of the cell wall. Throughout the development of mucilage cells of Araucaria angustifolia (Bertol.) Kuntze, a gradient of distribution was observed in relation to the pectic de-esterification, as well as to the increase of galactan and arabinan epitope distribution, and to the reduction of arabinogalactans proteins (AGPs) epitope at maturity. AGP and methyl-esterified homogalacturonan (HGA) were present in the mucilage. Galactans and arabinans were also observed in the mucilage, though with weak labelling. Degradation of AGP in the maturity of mucilage cells, in cell wall, as well as in the secretion, could be involved in the programmed cell death (PCD). Different labellings found among parenchyma and mucilage cells suggested differences in the cell wall properties of the mucilage cells.